A118 GUT MICROBIOTA TRANSPLANTATION FROM A PATIENT WITH SEVERE CONSTIPATION INDUCED CHANGES IN COLONIC FUNCTION AND STRUCTUR OF GNOTOBIOTIC MICE. (26th February 2020) - Bai, X; De Palma, G; Lu, J; Collins, S M; Bercik, P
Abstract: Background: Increasing evidence suggests that gut microbiota play a key role in gastrointestinal (GI) tract function. We have previously shown that fecal microbiota transplantation diarrhea predominant IBS patients into germ-free mice induces faster GI transit, increased permeability and innate immune activation. However, it is unknown whether gut dysfunction is induced by microbiota from patients with chronic constipation. Aims: Here, we investigated the role of the intestinal microbiota in the expression of severe slow transit constipation in a patient with previous C difficile infection and extensive antibiotic exposure. Methods: Germ-free (GF) mice (14 weeks old) were gavaged with diluted fecal content from the patient with constipation (PA) or a sex and age-matched healthy control (HC). 12 weeks later, we assessed gut motility and GI transit using videofluoroscopy and a bead expulsion test.. We then investigated intestinal and colonic smooth muscle isometric contraction in vitro using electric field stimulation (EFS), and acetylcholine (Ach) release was assessed by superfusion using [ 3 H] choline. Histological changes were evaluated by H&E and immunohistochemistry. Results: Mice with PA microbiota had faster whole GI transit (score 18.9 ± 0.9 (N=9) than mice with HC microbiota (15.4 ± 1.0, N=10, p=0.032), with markers located mainly in the distal small bowel and cecum. However, bead expulsion from the colon was significantly longer in PA mice (420.8 s ± 124.6 s, N=9) than in HC mice (82.6 s ± 20.0 s, N=10, p=0.026). This delayed colonic transit was likely due to colonic retroperistalsis visualized videofluoroscopically by retrograde flow of barium in the right colon of PA mice. There was no difference between the two groups in small intestinal or colonic tissues in Ach release or contractility induced by carbachol or KCl, . EFS caused transient biphasic relaxation and contraction in small intestine and colon, with the colonic contraction being stronger in the PA group. Microscopic tissue analysis showed disruption of the interstitial cells of Cajal (ICC) network and increased lymphocyte infiltration in colonic mucosa and submucosa in PA mice. Conclusions: These results indicate that the microbiota is a driver of delayed colonic transit in a patient whose constipation started following extensive antibiotic exposure for C. difficile infection. The observed dysmotility pattern was not due to lower muscle contractility but likely caused by immune mediated changes in the ICC network. Funding Agencies: CIHR